Ganz Salzburg bewegen [All of Salzburg Moving]: a large-scale public involvement project with underserved groups, for the co-design of local and contextualized physical activity promotion concepts - Stefan Tino Kulnik; Sybille Salbrechter; Stefanie Radwanovsky; Ulrike Garstenauer; Michael Ebner; Till Fuhrmeister; Andreas Stainer-Hochgatterer; Daniela Wurhofer; Melanie Roth (Research Involvement and Engagement)
Abstract Background Physical inactivity is a globally growing public health problem, contributing to significant disease burden (cardiovascular disease, diabetes, cancers, depression) and associated healthcare and societal costs. In Austria, several underserved groups (UGs) display lower than average physical activity (PA) levels, including people aged 30–45 and 60 + years, and those without employment, with minimal education level, or with migration background. PA promotion requires an approach that answers to local circumstances and the specific needs of UGs, to develop tailored and contextualized concepts. The public involvement project “Ganz Salzburg Bewegen” [“All of Salzburg Moving”] aimed to develop such concepts for UGs in the city of Salzburg, Austria. Methods In 2023, we conducted a large-scale participatory design process in the Lehen district of the city of Salzburg, involving citizens from UGs in needs assessment and ideation of concepts for PA promotion. Over 400 citizens engaged in a four-day community conversation event, eight citizen interviewers spoke with 53 peers, and 80 citizens participated in a two-day ideas workshop, co-designing PA promotion concepts together with design and PA promotion experts. Results The process resulted in 98 ideas addressing issues of inclusivity, accessibility and affordability of PA, and including aspects of community building and social participation to support engagement and motivation for PA. Ten ideas were selected, developed further in collaboration with design experts, and presented in a public exhibition at which citizens voted for their favourites with over 960 “likes”. Our evaluation showed that there was good representation from UGs, and that 90–97% of citizens were satisfied with their engagement in the project, felt they could adequately express their personal opinions, and thought they could comprehend the tasks and explanations for different activities well. The Public and Patient Engagement Evaluation Tool (PPEET) indicated overall good quality of involvement activities. Conclusions This public involvement project has successfully employed participatory design methods at large scale to catalyze change for PA in an urban setting. This practice example and our learnings throughout the process may offer transferable insights to others who plan participatory projects and co-design for PA promotion in the public domain and with UGs.